Growth and Nutritional Quality of Lemnaceae Viewed Comparatively in an Ecological and Evolutionary Context - Barbara Demmig-Adams; Marina López-Pozo; Stephanie K. Polutchko; Paul Fourounjian; Jared J. Stewart; Madeleine C. Zenir; William W. Adams (Plants, 2022)
This review focuses on recently characterized traits of the aquatic floating plant Lemna with an emphasis on its capacity to combine rapid growth with the accumulation of high levels of the essential human micronutrient zeaxanthin due to an unusual pigment composition not seen in other fast-growing plants. In addition, Lemna’s response to elevated CO2 was evaluated in the context of the source–sink balance between plant sugar production and consumption. These and other traits of Lemnaceae are compared with those of other floating aquatic plants as well as terrestrial plants adapted to different environments. It was concluded that the unique features of aquatic plants reflect adaptations to the freshwater environment, including rapid growth, high productivity, and exceptionally strong accumulation of high-quality vegetative storage protein and human antioxidant micronutrients. It was further concluded that the insensitivity of growth rate to environmental conditions and plant source–sink imbalance may allow duckweeds to take advantage of elevated atmospheric CO2 levels via particularly strong stimulation of biomass production and only minor declines in the growth of new tissue. It is proposed that declines in nutritional quality under elevated CO2 (due to regulatory adjustments in photosynthetic metabolism) may be mitigated by plant–microbe interaction, for which duckweeds have a high propensity.